Clinical manifestations, course, and outcome of patients with neutralizing anti-interferon-γ autoantibodies and disseminated nontuberculous mycobacterial infections. Issue 25 (June 2016) - Chi, Chih-Yu; Lin, Chia-Hao; Ho, Mao-Wang; Ding, Jing-Ya; Huang, Wen-Chi; Shih, Han-Po; Yeh, Chun-Fu; Fung, Chang-Phone; Sun, Hsin-Yun; Huang, Ching-Tai; Wu, Ting-Shu; Chang, Chih-Yen; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Neutralizing anti-interferon-γ autoantibody (nAIGA)-associated immunodeficiency is an emerging medical issue worldwide. In the present study, we describe and discuss the clinical features and outcomes of patients with nAIGAs and disseminated infections by nontuberculous mycobacteria (dNTM). We thoroughly reviewed the medical records of all patients. Microorganisms and nAIGAs were identified using previously described methods with modifications. All data were calculated and analyzed using SPSS software. Among 46 adult patients with dNTM infections, we identified 45 cases (97.8%) with nAIGAs. The average patient age was 58.6 years, and there was no sex predominance. Cervical lymphadenitis (81.8%) was the most common clinical manifestation. Endocrine disorder was the leading comorbidity (7 cases). Malignancies were found in 4 patients, and all of the malignancies originated from the T-cell/macrophage lineage. More than half of the identifiable isolates were slow-growing NTMs. Twenty-eight (62.2%) and 18 (40.0%) patients had a history of zoster and salmonellosis, respectively. A high proportion of patients with recurrent episodes of NTM infection or a history of zoster and dNTM infection had initial nAIGA titers ≥10 –5 dilution ( P  < 0.05). Twenty-seven patients (60.0%) required long-term antimycobacterial therapy and had at least 1 episode of recurrent NTM disease. No mortality was related to dNTM infection. In Taiwan, nAIGAs are a recently recognized mechanism of dNTM infection. Long term of antibiotic treatment and adherence to medical advice are necessary to improve the clinical outcome of patients with nAIGAs.